1995
DOI: 10.1177/105477389500400302
|View full text |Cite
|
Sign up to set email alerts
|

Sleep during the Week before Labor

Abstract: This correlational study was conducted to examine the relationship between maternal sleep during the nights prior to the onset of labor and labor outcomes of length, type of delivery, and maternal perceptions of labor. Subjects (N = 99) were drawn from childbirth education classes at a women's hospital in the southeastern United States. Subjects completed the Visual Analog Sleep Scale each morning, beginning two weeks prior to their due dates. Following delivery, subjects completed the Perception of Labor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The third trimester is identified as the period of pregnancy with the most disturbed sleep, including the highest number of midsleep awakenings. Evans, Dick, and Clark (1995) found low sleep effectiveness and high sleep disturbance scores for women during the third trimester. They also found that sleep quality continues to decrease through the last week of pregnancy and is lowest the night before labor.…”
Section: Discussionmentioning
confidence: 91%
“…The third trimester is identified as the period of pregnancy with the most disturbed sleep, including the highest number of midsleep awakenings. Evans, Dick, and Clark (1995) found low sleep effectiveness and high sleep disturbance scores for women during the third trimester. They also found that sleep quality continues to decrease through the last week of pregnancy and is lowest the night before labor.…”
Section: Discussionmentioning
confidence: 91%
“…Sleep is gaining recognition as an important factor to consider when studying or treating pregnant women. For example, many epidemiological reports have linked poor sleep or insomnia to poor health outcomes, including depression (Okun, Kiewra, Luther, Wisniewski, & Wisner, 2011;Okun, Kiewra, Luther, et al, 2011;Volkovich, Tikotzky, & Manber, 2016;Wolynczyk-Gmaj et al, 2017;Yang et al, 2017;Hux, Roberts, & Okun, 2017), preterm birth (Okun, Luther, Prather, et al, 2011;Blair, Porter, Leblebicioglu, & Christian, 2015;Li et al, 2016) and longer labor times (Evans, Dick, & Clark, 1995;Lee & Gay, 2004). The undisputed association between stress and sleep is particulary poignant in pregnancy, as stress is independently associated with poor pregnancy outcomes (Okun, Roberts, Begley, Catov, & Patrick, 2013;Palagini et al, 2014;Hux et al, 2017).…”
Section: Overview Of Sleepmentioning
confidence: 99%
“…Sleep disorders such as sleep-disordered breathing and insomnia, as well as poor sleep quality, circadian misalignment, and short sleep duration, are implicated in increased risk for adverse outcomes. Poor sleep quality, short sleep duration, and insomnia, for instance, are associated with new and recurrent depressive episodes (Bei et al, 2010;Dorheim, Bjorvatn, & Eberhard-Gran, 2012;Goyal, Gay, & Lee, 2007;Kamysheva, Skouteris, Wertheim, Paxton, & Milgrom, 2009;Okun, Hanusa et al, 2009;Okun, Luther et al, 2013;Skouteris, Wertheim, Germano, Paxton, & Milgrom, 2009), preterm birth (Guendelman et al, 2013;Micheli et al, 2011;Okun, Schetter, & Glynn et al, 2011 (Ayrim et al, 2011;Bourjeily et al, 2010;Champagne et al, 2009;O'Brien et al, 2012;Williams et al, 2010), labor and delivery outcomes (Beebe & Lee, 2007;Evans et al, 1995;Lee & Gay, 2004), and immune/endocrine dysregulation Okun, Luther, Prather et al, 2011;Okun, Luther, Wisniewski, & Wisner, 2013); and a few examined infant outcomes (Ayrim et al, 2011;Bourjeily et al, 2010;Franklin et al, 2000;Goyal, Gay, & Lee, 2009;Nishihara & Horiuchi, 1998). Sleep-disordered breathing, which involves hypoxia and sleep disruption, is similarly associated with the adverse outcomes and predominantly associated with preeclampsia, gestational diabetes, gestational hypertension, intrauterine growth restriction, and low birth weight (Carnelio, Morton, & McIntyre, 2017).…”
Section: Sleep and Adverse Pregnancy Outcomesmentioning
confidence: 99%